Communicationless Adaptive Control Strategy for Effective Reactive Power Sharing in a Grid-Independent AC Microgrid - D, Suchitra; D, Anitha; S, George Fernandez; Alaas, Zuhair Muhammed; Ali, Ziad M.; Abdel Aleem, Shady H. E. (Frontiers in Energy Research, 2022)
The microgrid (MG) ensures a reliable power supply as it can work in a grid-independent mode. This mode requires a coordinated control strategy among distributed generators (DGs). One major challenge in a grid-independent MG is the reactive power-sharing issue. The reactive power sharing is affected by the mismatch of feeder impedance and private loads. This study thus proposed a proportionate reactive power-sharing scheme in a grid-independent mode by mathematically computing the equivalent impedance without the need for communication lines. A mathematical formula is derived to compute the equivalent impedance as a function of the total power output of DG and the power fed to the feeder. Based on the computed equivalent impedance, the virtual impedance is added to each feeder. The inclusion of virtual impedance in each line compensates the mismatch in feeder impedance and private loads providing accurate reactive power sharing among DGs. MATLAB Simulink was used to verify the effectiveness of the proposed control strategy. Furthermore, the real-time OPAL-RT simulator was used to verify the results.